The Role of The Father in The Novel Ayah Menyayangi tanpa Akhir Karya Kirana Kejora: Analysis of Literary Psychology - Ningrum, Ayu (L'Geneus : The Journal Language Generations of Intellectual Society, 2019)
Literary work is considered as a masterpiece that has high life values, literature is able to evoke the human side that makes human readers become fully human. The writing of this thesis is done with the aim of obtaining an illustration of how the father's role is like a father who plays his role as a mother, a father who carry out his role as a playmate and so on in the novel Ayah Menyayang iTanpa Akhir by Kirana Kejora and what factors influence the psychology of a single father in the novel Ayah Menyayang Tanpa Akhir by Kirana Kejora. In order to achieve this goal, the writer examines Kirana Kejora's novel Ayah syaiangi (no end) by applying literary psychology theory. The problem in this thesis is limited to only describing the psychological aspects of the father character and the role of a father in the family, there are benefits of this research to enrich the study and appreciation of Indonesian literary works, helping readers understand the depiction of the role of the father and the psychological aspects of the single father in Kirana's novel Ayah Menyayangi Tanpa Akhir. Morning. The data analysis technique was carried out by descriptive analysis by connecting Kirana Kejora's novel Ayah Menyangi TanpaAkhir with literary psychology, so that four roles of father can be found, namely father as mother, as a playmate, as a good teacher, and as a quarrel partner.